Tārīkh-i ʿālam ārā-yi amīnī : Sharḥ-i ḥukmrāni-yi salāṭīn-i Āq Qūyūnlū wa ẓuhūr-i Ṣafawiyān - Khunjī, Faḍlallāh b. Rūzbihān (Miras Maktoob, ISBN: 9789004365452., 2019)
Born in Shiraz and a student of one of the founders of the Shiraz School in philosophy, Jalāl al-Dīn Dawānī (d. 908/1502-03), Faḍlallāh b. Rūzbihān Khunjī (d. 927/1521) was a scholar who wrote on a variety of subjects, with more than thirty titles to his name. In his younger years, Khunjī had travelled several times to Cairo and the Hejaz, studying the traditional Islamic sciences under a number of scholars there. The rest of his life he mostly spent in the eastern part of the Persianate world, moving from court to court as circumstances required. The work that is published here is historical, being a chronicle of the reign of the Aq Qoyunlu ruler Yaʿqūb b. Uzun Ḥasan (d. 896/1490) and the emergence of the Safavids, covering the years 882-96/1478-91. Based on a clear vision of historiography, this rare contemporary document, written from memory and oral sources, is largely a witness account of events.